Provisioning ecosystem services and direct drivers change in wetlands related to groundwater in Iberoamerica and Spain - Teresita Betancur; Emilia Bocanegra (Biota Colombiana, 2016)
Wetlands have been recognized as very important habitats to support the ecological processes in ecosystems. They supplie goods and ecosystem services for human well-being. Many wetlands are related to groundwater and depend from of them. This explains that some actions taken in aquifers affect the function of wetlands and can threaten their existence. The UNESCO-IGCP Project 604: Wetlands Related to Groundwater in Iberoamerica, has the objective to generate knowledge about the interaction between groundwater, wetlands and human activitiess in Ibero-America and Spain, by evaluating their main hydrological characteristics, the services these ecosystems provide to humans and the factors that may induce changes in such services. In the framework of this Project, researchers from 13 countries have provided information on the characteristics of 64 wetlands, on the aquifers linked to them, and a summary of their services. In this paper, the results obtained relative to provision of ecosystemic services have been summarized, as well as the main factors that could produce changes in them. The special reference to this type of services is due to the fact that the human socioeconomical activities may have a greater impact on them and produce the most important changes and impacts, especially in what refers to materials extraction, pollution, and land use.